Epidemiology and Ettiology of Orthopedic Accudents During the Work - Seyed Mohammad Ebrahim Mousavi (University of Social Welfare and Rehabilitation Sciences, 2002)
Objective: Work accidents and injuries are important issues because it usually happens for the young and active population in the society. Every year, lots of workers in the country loss their productivity and health because of work accident. The aim of this study is to find the main causes of accidents and injuries at work and suggesting the possible prevention solutions. Materials & Methods: The study was done in Fayyazbakhsh hospital which is the most active hospital in referring work injuries. For one month, 320 patients related to work injury participated in the study. Results: Most injuries were related to the hand and they were severe. The most important factors in work accidents were psychic problems, past illness history, lack of education, budget problem and not using safety tools and helmet during the work. Conclusion: It is necessary to pay attention to problems which target workers, employees, insurance organizations, welfare institutes and finally society.